Teenagers Expand Their Conceptions of Climate Change Adaptation Through Research-Education Cooperation - Schrot, Oliver Gerald; Keller, Lars; Peduzzi, Dunja; Riede, Maximilian; Kuthe, Alina; Ludwig, David (Climate Change and the Role of Education, 2019)
Unlike previous generations, today’s youth is directly affected by global anthropogenic climate change (CC), and its increasing consequences throughout their lifetimes. However, both the educational strategies to prepare them for CC adaptation, and their conceptions of CC adaptation, remain insufficiently understood. This study sets out to investigate the CC adaptation conceptions of 120 students from four high-schools in Austria and Italy. The influence of a year-long research-education cooperation between students and 28 CC adaptation experts is examined. In the educational design, the focus lies on moderate-constructivist theories, and the transdisciplinary dialogue between students and experts. A mixed-methodologies approach is applied, which combines content analysis to study students’ conceptions of CC adaptation and test statistics (chi-square and t-test) to assess the impact of the educational intervention. The results show that students’ conceptions differ in degree of sophistication, and also include misconceptions. Some students relate adaptation to limiting disadvantages due to CC, others confuse adaptation with mitigation or environmental protection. After the educational intervention, most students have expanded their CC adaptation conceptions and overcome misconceptions, and their performance to differentiate between adaptation and mitigation increased significantly. This paper will be useful to researchers and teachers interested in utilizing education as a means to adapting to CC.
Keywords: Adaptation; Climate change; Collaborative research; Conceptual change; Constructivist learning